Handbook of research on developing engaging online courses - Thornburg, Amy W. (IGI Global, 2020)
Online instruction is rapidly expanding the way professors think about and plan instruction. In addition, online instructional practices are expanding and changing as new tools and strategies are adopted. It is imperative that programs and institutions of higher education explore increased online options that align with best practices to develop effective and engaging online courses. The Handbook of Research on Developing Engaging Online Courses is an essential research publication that provides multiple perspectives on improving student engagement and success in online courses. This book incl